The Influence of Wedge Sea Hare (Dolabellaauricularia) Extract and Papaya Juice on Hemoglobin (Hb) and Feritin Levels of Mice Strain (Balb / C) with Anemia (Medico Legal Update, 2020)
The aim was to see the effect of wedge sea hare extract and papaya juice, on Hemoglobin and Ferritin levels of Mice Strain (BALB / c).Method, True Design Experiment with Control Group, has been used. Mice were divided into 5 groups, each group 5 tails, reserves 5 tails. Intervention of mice was given a solution of collaborative compounds (a mixture of sea rabbit extract with papaya juice) for 21 days, with the distribution of the following doses: Group A, Control (-), Group B, Control (+), Fe tablets 0.65 mg / kg BW, Group C, dose treatment = 100 mg / kg BW of mice / day, Group D, dose treatment = 150 mg / kg BW of mice / day, Group E, dose treatment = 250 mg / kg BW mice / day. Blood is taken before and after treatment 21 days. Data Analysis using a Paired t-test and ANOVA statistical tests.The results, statistical tests showed a significant difference in hemoglobin levels that were significant in the three treatments, between before and after treatment, with P